2017
DOI: 10.3329/sja.v15i1.33147
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weather factors on the abundance and population dynamics of Spodoptera litura F. and Pieris brassicae L. on cabbage

Abstract: In order to study the influence of weather factors on the abundance and population dynamics of Spodoptera litura F. and Pieris brassicae L. on cabbage, a field experiment was conducted. Larval population of S. litura ranged from 0.56 to 1.57 larvae/plant during 8 January to 12 February 2014 crop season while the highest peak was on 5 February 2014 (1.57 larvae/plant) at 29.5 0 C temperature. In case of Pieris brassicae, larval population ranged from 0.58 to1.98 larvae/plant and the highest peak of P. brassicae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
1
4
1
1
Order By: Relevance
“…However, maximum and minimum temperature had negative effect on their population, as the correlates were highly significant and negative. However, the present findings are in contradiction with those of Khan and Talukder (2017) who found that the population of P. brassicae was positively correlated with maximum and minimum temperatures while negative correlation with maximum relative humidity and a strong negative correlation minimum relative humidity.…”
Section: Seasonal Incidence Of P Brassicae On Cabbagecontrasting
confidence: 57%
“…However, maximum and minimum temperature had negative effect on their population, as the correlates were highly significant and negative. However, the present findings are in contradiction with those of Khan and Talukder (2017) who found that the population of P. brassicae was positively correlated with maximum and minimum temperatures while negative correlation with maximum relative humidity and a strong negative correlation minimum relative humidity.…”
Section: Seasonal Incidence Of P Brassicae On Cabbagecontrasting
confidence: 57%
“…The results revealed that moth catches and larval population of S. litura (each) had significant positive correlation with maximum temperature (r=0.461 and 0.523, respectively), minimum temperature (r=0.613 and 0.422, respectively), rainfall (r=0.711 and 0.444, respectively) and rainy days (r=0.703 and 0.406, respectively).The egg-masses of S. litura showed significant negative correlation with morning relative humidity (r = -0.768) and minimum temperature (r= -0.624). This finding was in confirmation with the reports of Khan and Talukder (2017), Radhika (2013) and Prasannakumar et al (2012) who reported strong positive correlation of temperature (minimum and maximum) and negative correlation of relative humidity (morning and evening) with the population of S. litura in cabbage, groundnut and potato.…”
Section: Effect Of Weather Parameters On Seasonal Dynamics Of S Liturasupporting
confidence: 92%
“…These results agreed with those of Mitchell et al, (1991) who reported that in the tropics, S. frugiperda populations have a tendency to vary with changes in rainfall. Khan and Talukder (2017) reported a significant negative correlation between larval population of diamondback moth and rainfall.…”
Section: Resultsmentioning
confidence: 98%